Valley-selective Landau-Zener oscillations in semi-Dirac p − n junctions - Saha, K; Nandkishore, R; Parameswaran, S (American Physical Society, 2017)
We study transport across p-n junctions of gapped two-dimensional semi-Dirac materials: nodal semimetals whose energy bands disperse quadratically and linearly along distinct crystal axes. The resulting electronic properties - relevant to materials such as TiO2/VO2 multilayers and α-(BEDT-TTF)2I3 salts - continuously interpolate between those of mono- and bilayer graphene as a function of propagation angle. We demonstrate that tunneling across the junction depends on the orientation of the tunnel barrier relative to the crystalline axes, leading to strongly nonmonotonic current-voltage characteristics, including negative differential conductance in some regimes. In multivalley systems, these features provide a natural route to engineering valley-selective transport.